The Kodak Girl: publicity images of women in the heyday of analogue photography (ModaPalavra e-periódico, 2023)
In a period when technological innovations such as the bicycle revolutionized the role of women in society (Strange, 2002), it is opportune to observe how photographic technology and one of its most significant representatives (the Kodak “domestic” camera) are associated with the female public. This article aims to carry out an evaluation of the female profile presented by Kodak advertising pieces throughout the 20th century, from the first decade to the 1980s. This period reflects the heyday of darkroom photography, precisely the technology that Kodak helped to disseminate. The study was carried out through a literature review and iconographic survey, which supported an evaluation of the evolution of the company's advertising and the way in which women are represented.
Keywords: advertising; representation of woman; photographie